Biocompatibility of cerium dioxide and silicon dioxide nanoparticles with endothelial cells - Strobel, Claudia; Förster, Martin; Hilger, Ingrid (Beilstein Journal of Nanotechnology, 2014)
Cerium dioxide (CeO2) and silicon dioxide (SiO2) nanoparticles are of widespread use in modern life. This means that human beings are markedly exposed to them in their everyday life. Once passing biological barriers, these nanoparticles are expected to interact with endothelial cells, leading to systemic alterations with distinct influences on human health. In the present study we observed the metabolic impact of differently sized CeO2 (8 nm; 35 nm) and SiO2 nanoparticles (117 nm; 315 nm) on immortalized human microvascular (HMEC-1) and primary macrovascular endothelial cells (HUVEC), with particular focus on the CeO2 nanoparticles. The characterization of the CeO2 nanoparticles in cell culture media with varying serum content indicated a steric stabilization of nanoparticles due to interaction with proteins. After cellular uptake, the CeO2 nanoparticles were localized around the nucleus in a ring-shaped manner. The nanoparticles revealed concentration and time, but no size-dependent effects on the cellular adenosine triphosphate levels. HUVEC reacted more sensitively to CeO2 nanoparticle exposure than HMEC-1. This effect was also observed in relation to cytokine release after nanoparticle treatment. The CeO2 nanoparticles exhibited a specific impact on the release of diverse proteins. Namely, a slight trend towards pro-inflammatory effects, a slight pro-thrombotic impact, and an increase of reactive oxygen species after nanoparticle exposure were observed with increasing incubation time. For SiO2 nanoparticles, concentration- and time-dependent effects on the metabolic activity as well as pro-inflammatory reactions were detectable. In general, the effects of the investigated nanoparticles on endothelial cells were rather insignificant, since the alterations on the metabolic cell activity became visible at a nanoparticle concentration that is by far higher than those expected to occur in the in vivo situation (CeO2 nanoparticles: 100 µg/mL; SiO2 nanoparticles: 10 µg/mL).
Keywords: cerium dioxide; endothelial cells; nanoparticle; nanotoxicology; silicon dioxide